LEVEL OF UNDERSTANDING AND REASONS CUSTOMERS CHOOSE SHARIA INSURANCE PRODUCTS - Delvia Rusita Purnamasari; Azhar Alam (Universitas Airlangga, 2020)
This study aims to determine the level of customer understanding of Islamic insurance products and reasons for customers to buy or become consumers of Islamic insurance. This research uses a quantitative approach with descriptive statistical analysis. This research took at PT. Solo Family Takaful of 100 respondents. The data collection method uses a questionnaire distributed to customers, and the data processing uses the Guttman Scale Cross-Sectional model (traditional) with the help of Microsoft Excel 2010 and SPSS 24. The results of this study indicate that the level of understanding and reasons for customers in choosing sharia insurance products are classified as high due to factors consumer interest and knowledge factors.